2022
DOI: 10.21037/tp-21-424
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth and intelligence quotient in children with Down syndrome

Abstract: Background: The relationship between intelligence quotient (IQ) and somatic development, especially growth, has been demonstrated in various groups of children. Down syndrome (DS) is characterized by short stature, overweight, and cognitive impairment. The objective of our work was to assess whether anthropometric measurements [weight, height, body mass index (BMI)] of children with DS correlate with their IQ. The results of the study may be valuable for this population in the light of increasing access to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A study by Kłosowska et al. (2022) suggested that the height percentile of children with DS correlates with their IQ. These observations may be valuable in expanding our understanding of the cognitive function of people with DS when correlating growth parameters, such as height, to the imaging, and IQ test results in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kłosowska et al. (2022) suggested that the height percentile of children with DS correlates with their IQ. These observations may be valuable in expanding our understanding of the cognitive function of people with DS when correlating growth parameters, such as height, to the imaging, and IQ test results in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal subregions (dentate gyrus, Ammon's horn, and subiculum) are crucial to understanding the role of hippocampal formation and its association with the memory domain. A study by Kłosowska et al (2022) suggested that the height percentile of children with DS correlates with their IQ.…”
Section: Discussionmentioning
confidence: 99%
“…The intelligence quotient (IQ) is critical in assessing the neurological and cognitive development of children with DS. It may also reflect their physical and somatic growth, as documented by Kłosowska et al [ 14 ]. Therefore, establishing a connection between the brain's metabolic profiles and IQ in children with DS could provide insights into the underlying reasons for this relationship and aid in developing strategies to improve their IQ.…”
Section: Introductionmentioning
confidence: 97%
“…Comorbidities associated with Down syndrome further contribute to the complexity of providing comprehensive care to this population [23][24][25]. Cognitive impairment in individuals with Down syndrome can range from mild (with an IQ between 50 and 70) to moderate (with an IQ between 35 and 50), and occasionally, it can be severe (with an IQ between 20 and 35) [26,27]. Additionally, individuals with Down syndrome face a significant risk of experiencing hearing loss (75%), obstructive sleep apnea (50% to 79%), otitis media (50% to 70%), eye-related issues (60%) including cataracts (15%) and severe refractive errors (50%), congenital heart defects (50%), neurological dysfunction (ranging from 1% to 13%), gastrointestinal atresias (12%), hip dislocation (6%), and thyroid disorders (ranging from 4% to 18%) (Table 1) [28].…”
Section: Introductionmentioning
confidence: 99%